The heist [compact disc, unabridged] - Cussler, Clive; Du Brul, Jack B. (Cussler, Clive. Isaac Bell adventure (Sound recording), 2024)
In the summer of 1914, Isaac Bell attends a private meeting on Woodrow Wilson's presidential yacht, as Wilson addresses the newly launched regional Federal Reserve banks. Bell is present as a security agent with his father, who will be the head banker of the Boston region. Just after Wilson introduces a plan for new currency notes, the yacht comes under attack from a bi-wing airplane. Bell shoots down the plane with a machine gun and saves everyone aboard. But the attack on the yacht was only the first of Bell's problems. While responding to a curious murder scene in Rhode Island, he learns of a heist planned for the new federal printing and engraving building in D.C., where the new currency has been printed. Bell must track down the thieves and the currency before the new Federal Reserve system, and America's economy, is destroyed.